ANALISA KEPUTUSAN PEMBELIAN DETERJEN SOKLIN SMART DITINJAU DARI KELOMPOK REFERENSI, KUALITAS PRODUK DAN PROMOSI DI KABUPATEN WONOGIRI - Budi Rahayu; Djumali Djumali; Sudarwati Sudarwati (ITB AAS INDONESIA Surakarta, 2019)
The research aims to find out and describe the influence of either simultaneously or partial reference groups, product quality and promotion to purchasing decision for Soklin Smart Detergent in Wonogiri District. This research using quantitative descriptive research. The population was all consumer Soklin Smart Detergent in Wonogiri District unknown number. The number of samples was determined with the formula Sarwono and the result 100 respondents. Sampling method using accidental sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis. This F test results the reference groups, product quality and promotion simultaneously and significant effect to purchasing decision for Soklin Smart Detergent in Wonogiri District. The t-test results showed that the reference groups influential positive and significant effect against to purchasing decision for Soklin Smart Detergent in Wonogiri District. Product quality influential positive and significant effect against to purchasing decision for Soklin Smart Detergent in Wonogiri District. Promotion influential positive and significantly to purchasing decision for Soklin Smart Detergent in Wonogiri District. The results of the determination of the coefficient indicates the reference groups, product quality and promotion have influence of 57,2% the purchasing decision for Soklin Smart Detergent in Wonogiri District. The most dominant influence to purchasing decision for Soklin Smart Detergent in Wonogiri District is product quality because it has the most tvalue is 6,654. Keywords: Purchasing Decision, Reference Groups, Product Quality, Promotion